1991
DOI: 10.1557/jmr.1991.2208
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural development and electrical properties of sol-gel prepared lead zirconate-titanate thin films

Abstract: A systematic investigation of the microstructural evolution of fast fired, sol-gel derived Pb(Zr, Ti)O3 films (Zr/Ti = 54/46) was performed by analytical transmission electron microscopy (TEM). It was found that the nucleation and growth of the sol-gel PZT films were influenced by the precursor chemistry. The precursor solution was composed of Pb 2-ethylhexanoate, Ti isopropoxide, and Zr n-propoxide in n-propanol. Porous and spherulitic perovskite grains nucleated and grew from a pyrochlore matrix for NH4OH-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Earlier studies on the fabrication of PZT thin film using the sol-gel method mainly concentrated on the transformation of the amorphous gel film to the perovskite phase during annealing. 2,[5][6][7][8][9] Recently, many studies on the control of the preferred orientation of the PZT films on various substrates have been reported because the preferentially oriented or epitaxial films show better electrical properties: the P-E hysteresis and the pyroelectric coefficient. 1,2 Since the nucleation is the rate-limiting step in the perovskite transformation, the creation of numerous heterogeneous nucleation sites is important to achieve the perovskite phase formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on the fabrication of PZT thin film using the sol-gel method mainly concentrated on the transformation of the amorphous gel film to the perovskite phase during annealing. 2,[5][6][7][8][9] Recently, many studies on the control of the preferred orientation of the PZT films on various substrates have been reported because the preferentially oriented or epitaxial films show better electrical properties: the P-E hysteresis and the pyroelectric coefficient. 1,2 Since the nucleation is the rate-limiting step in the perovskite transformation, the creation of numerous heterogeneous nucleation sites is important to achieve the perovskite phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…The films were fabricated with different coating cycles (3,5,7,9,11), dried at 330 ± C for different holding times (5, 30, 60 min), and then annealed at the same temperature of 650 ± C using rapid thermal annealing (RTA). Effects of the holding time for pyrolysis and the coating cycle on the preferred orientation of the PZT thin films were studied.…”
mentioning
confidence: 99%
“…1 " 3 Thin films of LiNbO 3 are of current research interest because of the demand for active integrated optical devices. 10 " 12 It has also been shown that the structure of sol-gel derived LiNbO 3 thin films sensitively depends on the prior processing. 7 " 9 Processing parameters such as solution chemistry, deposition technique, firing conditions, and substrate are known to influence the development of film crystallinity, porosity, grain size, and growth morphology during solgel processing.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated depositions followed by firing at elevated temperature are required to prepare thick films using these processes. Furthermore, sol-gel processing and screen-printing require high post-deposition processing temperatures to anneal the films to achieve the perovskite crystal structure [5,6]. The high processing temperature limits the overall film thickness because of cracking caused by thermal expansion mismatch with the substrate.…”
Section: Introductionmentioning
confidence: 99%